Cooperative learning strategy type STAD for economic business in SMK Bhakti Bangsa - Muhammad Fasya Fanshary Aksa; Maya Gita Cahyani; Amanda Tri Damayanti (Universitas Pendidikan Indonesia, 2023)
This research aims to evaluate the effectiveness of implementing Student Team Achievement Division (STAD) type cooperative learning strategies in increasing students' interest in learning in Business Economics subjects at BPI Bandung Vocational High Schools (SMK). Evaluation will include comparing student learning outcomes before and after implementing the STAD method, an analysis of student involvement in the cooperative learning process, and student responses to this learning method. Additionally, the research will highlight changes in interactions between students, their confidence in understanding the material, and whether implementing STAD can stimulate active participation in class discussions. The research uses a qualitative approach to explore the influence of the STAD strategy on students' interest in learning with observation and interviews related to implementing the STAD strategy. This qualitative analysis identifies patterns and findings that strengthen the effectiveness of the STAD strategy in increasing student interest and motivation to learn at SMK Bhakti Bangsa Bandung, especially in Business Economics subjects.